Handlebody Splittings of Compact 3-Manifolds with Boundary - Suzuki, Shin’ichi (Revista Matemática Complutense, 2007)
The purpose of this paper is to relate several generalizations of the notion of the Heegaard splitting of a closed 3-manifold to compact, orientable 3-manifolds with nonempty boundary.